Mechanical property of polypropylene with kenaf fiber wood flour composite / Mohd Syahir Abd Karim - Abd Karim, Mohd Syahir (2008)
As industry attempts to lessen the dependence on petroleum based fuels and products there is an increasing need to investigate more environmentally friendly, sustainable materials to replace existing materials. The research done in this study has proven the ability to successfully fabricate kenaf-polypropylene composites into sheet form. Kenaf fiber used was in form of flour or wood powder. The PP/kenaf composite shows the increase the impact strength at 10% to 30% by weight of the polypropylene powder. The use of coupling agent Maleic Anyhdride enabled successful fiber-matrix adhesion and increased the mechanical property of the PP/kenaf composite